2019
DOI: 10.1177/1076029619888026
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation and Transjugular Intrahepatic Portosystemic Shunting for Treatment of Portal Vein Thrombosis in Cirrhosis: A Systematic Review and Meta-Analysis

Abstract: Portal vein thromboses (PVTs) are associated with hepatic decompensation, worse survival, and worse liver transplant outcomes. We evaluated the impact of anticoagulation (AC) and transjugular intrahepatic portosystemic shunting (TIPS) on recanalization and mortality in patients with cirrhosis and PVT. Systematic search of electronic databases was performed. Clinical trials and observational studies that evaluated primary outcomes of recanalization and survival in patients with cirrhosis having PVT treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Anticoagulation (AC) represents the first-line therapeutic strategy for PTV. In a systematic review [21] and a recent prospective observational study [22], the efficacy of AC and TIPS placement in PVT were compared. Both strategies were found to be effective in achieving portal vein recanalization.…”
Section: Tips Toward Liver Transplant: Role and Timingmentioning
confidence: 99%
“…Anticoagulation (AC) represents the first-line therapeutic strategy for PTV. In a systematic review [21] and a recent prospective observational study [22], the efficacy of AC and TIPS placement in PVT were compared. Both strategies were found to be effective in achieving portal vein recanalization.…”
Section: Tips Toward Liver Transplant: Role and Timingmentioning
confidence: 99%
“…I n a m e t a -a n a l y s i s c o m p a r i n g t h e e f f i c a c y o f anticoagulation and TIPS placement for PVT, 7 studies (4 for anticoagulation and 3 for TIPS placement) were included. Anticoagulation and TIPS placement were evaluated in 179 and 148 patients, respectively (50). The analysis demonstrated that both treatments led to improved recanalization rates when compared to a control group.…”
Section: Tips Placementmentioning
confidence: 99%